2020
DOI: 10.1096/fj.201901951rr
|View full text |Cite
|
Sign up to set email alerts
|

Potential contribution of ryanodine receptor 2 upregulation to cGMP/PKG signaling‐induced cone degeneration in cyclic nucleotide‐gated channel deficiency

Abstract: Abbreviations: ATF6, activating transcription factor 6; CaMKII, calmodulin-dependent protein kinase II; cAMP, cyclic adenosine monophosphate; CAR, cone arrestin; cGMP, cyclic guanosine monophosphate; CHOP, CCAAT-enhancer-binding protein homologous protein; CNG, cyclic nucleotide-gated; CREB, cyclic adenosine monophosphate response element-binding protein; ER, endoplasmic reticulum; eIF2α, eukaryotic translation initiation factor 2 alpha; GFAP, glial fibrillary acidic protein; HRGP, human red/green pigment; Iba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 87 publications
(136 reference statements)
0
15
0
Order By: Relevance
“…In line with a neuroprotective effect of Prkg2-deletion, the levels of p-eIF2a were reduced to a level similar to Cnga3/Nrl/Gucy2e TKO mice (Figure 5c,d), which are protected from cGMP-mediated cytotoxicity due to the lack of the cGMP-synthesizing retGC enzyme [13]. Previous studies have demonstrated that CNG channel-deficient mice show increased expression/activity of ER Ca 2+ -releasing channels, responsible for Ca 2+ efflux from the ER into the cytosol [20,21]. We, therefore, analyzed the gene expression of Itpr1, which encodes the inositol 1,4,5-trisphosphate receptor type 1 (IP3R1), and Ryr2, the gene encoding the type 2 ryanodine receptor (Ryr2).…”
Section: Resultsmentioning
confidence: 67%
See 4 more Smart Citations
“…In line with a neuroprotective effect of Prkg2-deletion, the levels of p-eIF2a were reduced to a level similar to Cnga3/Nrl/Gucy2e TKO mice (Figure 5c,d), which are protected from cGMP-mediated cytotoxicity due to the lack of the cGMP-synthesizing retGC enzyme [13]. Previous studies have demonstrated that CNG channel-deficient mice show increased expression/activity of ER Ca 2+ -releasing channels, responsible for Ca 2+ efflux from the ER into the cytosol [20,21]. We, therefore, analyzed the gene expression of Itpr1, which encodes the inositol 1,4,5-trisphosphate receptor type 1 (IP3R1), and Ryr2, the gene encoding the type 2 ryanodine receptor (Ryr2).…”
Section: Resultsmentioning
confidence: 67%
“…As depicted in Figure 5e,f, both genes showed enhanced gene expression levels in the Cnga3 KO context, which were normalized after additional knockout of Prkg2. A similar effect was observed for the unfolded protein response (UPR)-related genes Atf6b (activating transcription factor 6 beta), Bax (Bcl2-associated X protein), Cebpb (CCAAT/enhancer-binding protein beta), Creb3l3 (cAMP-responsive element-binding protein 3-like 3), Derl1 (degradation in ER protein 1), Dnajc3 (DnaJ [Hsp40] homolog, subfamily C, member 3), Ern2 (ER to nucleus signaling 2), Ganc (glucosidase, alpha; neutral C), Srebf2 (sterol regulatory element-binding factor 2), and Uggt2 (UDPglucose glycoprotein glucosyltransferase 2; Figure 5e-g), which are upregulated in Cnga3deficient mice [19,21]. This suggests that Prkg2 knockout counteracts ER stress and UPR and normalizes ER homeostasis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations